Decorators in Python (Pragmatic AI Solutions, 2021)
Learn how to create a Python decorator that can handle exceptions by taking arguments and handling them automatically, saving you time and preventing repetition! In this video I'll walk you through some of the inner workings of decorators, but most importantly, I'll show you how to build a decorator that takes arguments and handles exceptions automatically, avoiding repetition and making your code more readable!